Unintentional childhood injury mortality in Europe 1984–93: a report from the EURORISC Working Group. Issue 3 (1st September 1999) - Morrison, Anita; Stone, David H
Abstract : Objective —To examine recent trends in unintentional childhood injury mortality in Europe, and to identify the contribution of specific causes. Setting —The 15 current member countries of the European Union. Methods —Analysis of mortality data (1984–93) obtained from the World Health Organisation and national government agencies. Results —Injuries continue to be the leading cause of childhood death in all study countries, with more than 4500 fatalities annually, accounting for over 30% of all child mortality. The major causes of death in all countries were injuries due to motor vehicle traffic accidents, drownings, fire and flames, and falls. Portugal experienced mortality rates double those of most other countries, with the differentials particularly stark early in the study period. Although a decrease in age standardised mortality rates was observed in all countries over the decade, the extent of the decrease varied widely, from −47% in the UK to −11% in Finland. Conclusion —The pattern of childhood injury in Europe is similar to that observed elsewhere in the world. None the less, differences in rates of childhood injury mortality persist between countries. Identifying the reasons for these variations between countries may hold the key to the reduction injury rates in Europe as a whole.